Runaway globalization and the cultural imagination of dependency - Jenkeri Zakari Okwori (Tydskrif vir Letterkunde, 2018)
This essay argues that globalisation is nothing but a renewed ideological onslaught by the western powers to reify their culture of racialised subjugation of Africa and other third world countries. To do so they persistently resort to the age old untenable argument that climate and geography are responsible for Africa’s underdevelopment. Apart from shifting the blame of Africa’s crises away from the effects of their direct actions, the climatic and geographic justifications for the African crises is an attempt to justify racial inequality which works to the political and economic advantage of the West. Globalisation and globalism by their nature and design therefore work hand in hand to ensure a hegemonic consciousness among Africans such that even their responses to globalisation is imagined and mediated from the pedestal of dependence, thereby entrapping them further into the conspiracy of Western globalised world. The way out for Africa is to respond to globalisation via the prism of “globalisation from below”, that is, to continue to determine their terms for partaking in the global in the context of their own existence.